Toward a Pragmatist Account of Human Practices (Nóema, 2022)
This paper focuses on a curious lacuna in the pragmatist tradition. In the writings of the classical American pragmatists (Peirce, James, Dewey, Mead, and Lewis) very little attention is given to articulating a conception of practices and, more broadly, of pragmata. The author offers a sketch of what he takes to be a pragmatist account of human practices. He stresses how for the pragmatists themselves theory is a practice or, more precisely, an extended family of evolving practices complexly related to other practices. Moreover, he takes such an account of practices to be fundamentally at odds with various attempts to provide a transcendental justification for any human practice. He draws upon a brief yet suggestive discussion in William James's Pragmatism of language, law, and truth and develops the implications of James's treatment of these topics. In the course of doing so, he proposes how a classic work (such as a philosophical text or musical composition) can be understood from a strictly historicist perspective. He concludes with a reflection on the extent to which creative intelligence has been conscripted by the bellicose agenda of national or imperialistic regimes, yet holds out the hope of creative intelligence freeing itself to some extent from the war machine of nation states.